A quantum chemistry approach to the force fields of the asymmetrical thionyl halides FS(O)Cl, CF3S(O)F and CF3S(O)Cl - Coronel, Angelina del Carmen (2011)
The vibrational properties of the asymmetrical thionyl halides FS(O)Cl, CF3SS(O)F and CF3SS(O)Cl were studied by means of density functional theory (DFT) techniques. The available experimental data and assignments for these molecules were compared with the theoretical results and revised. These data were subsequently used in the definition of the corresponding scaled quantum mechanics (SQM) force fields. A set of internal force constants was also calculated from such force fields.